Importance of the Composition of Semantic Fields in Learning about them - María Jesús Sánchez (Miscelánea: A Journal of English and American Studies, 2003)
First of all, the aim is to test whether in the semantic domains Classroom/Lab. and Cognitive, by means of a Pretest/Posttest design, learning is produced by the effect of the independent variable instruction. For this purpose, two tasks will be used: a written test and relationship judgements and four dependent variables: translation/definition test, proximity, distance and similarity. Secondly, it is tested in which semantic field the most learning takes place. This is explained by associative strength, which is produced by composition factors of the semantic field: origin of the terms and degree of concreteness. These results are in line with structural theory (Bajo, Cañas, Navarro, Padilla & Puerta, 1994) and concreteness theory (Harris, Tebbee & Leka, 1997; Marschark, 1992).